2014
DOI: 10.1111/anae.12878
|View full text |Cite
|
Sign up to set email alerts
|

Defining and developing expertise in tracheal intubation using a GlideScope® for anaesthetists with expertise in Macintosh direct laryngoscopy: an in‐vivo longitudinal study

Abstract: SummaryAlthough videolaryngoscopy can provide excellent views of the laryngeal structures as both the primary method of tracheal intubation and as a rescue technique for difficult direct laryngoscopy, the existing literature is inadequate to define expertise or even competence. We observed the performance of nine trainees during 890 intubations, with an additional 72 intubations performed by expert anaesthetists used as a control group. Univariate and multivariate mixed-effects logistic regression models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 26 publications
0
59
1
2
Order By: Relevance
“…This phenomenon is well known and described as a typical GlideScope intubation problem, which may be overcome with improved handling, such as shifting the blade to the left, backing up, holding the tube more proximally, and retracting the stylet as soon as the vocal cords are passed (12). Accordingly, there is strong evidence that expertise in video laryngoscopy requires prolonged training and practice, and a minimum of 76 attempts are considered necessary to achieve proficiency (32,33). The disappointing GlideScope (Verathon) performance in our study is a clear indicator that the learning process has just begun.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is well known and described as a typical GlideScope intubation problem, which may be overcome with improved handling, such as shifting the blade to the left, backing up, holding the tube more proximally, and retracting the stylet as soon as the vocal cords are passed (12). Accordingly, there is strong evidence that expertise in video laryngoscopy requires prolonged training and practice, and a minimum of 76 attempts are considered necessary to achieve proficiency (32,33). The disappointing GlideScope (Verathon) performance in our study is a clear indicator that the learning process has just begun.…”
Section: Discussionmentioning
confidence: 99%
“…8 Similarly, in a recently published clinical trial regarding the learning curve for GVL-facilitated tracheal intubation, obtaining a grade 1 view was included as one of four indicators of ''optimal performance'' with the device. 9 In contrast, other reported series have indicated that passage of the endotracheal tube (ETT) has sometimes been difficult despite obtaining a good view of the larynx during indirect VL. 10,11 Subsequently, a number of publications included the observation that maximizing glottic exposure during GVL video laryngoscopy may, in fact, make tracheal intubation more difficult, [12][13][14][15] and they have proceeded to recommend obtaining a more restricted view of the larynx.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we should consider the problem of learning curve, skill development and maintenance; video devices offer an incredible opportunity of didactic potential, allowing difficulty sharing and targeted help and teaching. On the other hand, it has been recently shown that learning curve for video laryngoscopes is not so obvious as it was in the past 22 , and it could take more than 75 attempts 23 to have perfect performance of video laryngoscopy as compared with 47 described in a classic paper by Mulcaster et al 24 for Macintosh laryngoscope.…”
Section: Seeing Is Not Survivingmentioning
confidence: 99%